Penanganan masalah turnover intention pekerja industri kreatif di Jakarta - Indira Safirawarman; Justine Tanuwijaya; Andreas Wahyu Gunawan Putra (Universitas Kristen Maranatha, 2024)
This study’s focus is aimed to analyze the turnover intention of creative industry workers in Jakarta, by analyzing the effect of perceived organizational support, work-family conflict, and supervisor support to turnover intention. The number of samples in this study are 116 respondents who work in creative industries. The sampling itself was taken using a purposive sampling method. The data collection instrument collected by online questionnaire using Google Form. The data analysis method uses descriptive statistics and SEM (Structural Equation Modeling) with SmartPLS software. The results of this study found there is an effect of perceived organizational support on work-family conflict, in addition to work-family conflict on turnover intention, but the same thing does not apply to supervisor support. The managerial implication of this research is that companies in the future is able to pay attention more to the forms of support for employees that aim to support their welfare while working at the company. Suggestions for the next similar research can focus on factors that can reduce the level of employee turnover intention, even though there is work-family conflict happen in workers.